INFLECTIONAL WORDS AND THEIR PROCESSES IN ENGLISH CHILDREN STORIES - Rudi Suherman; Lia Maulia Indrayani; Ekaning Krisnawati (Elite : English and Literature Journal, 2018)
A Story is an effective media in nurturing language development particularly for children. A children story should be appropriated with its readers. One of its appropriateness indicator can be investigated by seeing its morphological aspect like inflectional words in it. This study is aimed at investigating the inflectional words and their types in English children story which may indicate its level of difficulty and its function. The descriptive qualitative study is employed embracing the characteristics of document analysis. The data taken from three different children stories which then are analyzed utilizing the inflectional theory proposed by Booij (2008). It is found that the verb inflection and adjective inflection, respectively, become predominant inflection that can be found on every story. It may indicate that children stories emphasize on process of doing and process of describing thing The finding is also drawn a conclusion that the length of the story is in line with the number of inflectional words.Keywords: Inflectional words, Children story, Morphology.                                                             Abstrak Dongeng merupakan media yang efektif dalam meningkatkan perkembangan bahasa terkhusus pada anak- anak. Sebuah dongeng anak mestilah disesuaikan dengan para pembacanya. Salah satu indikator kebersesuaian ini bisa ditelaah dari aspek – aspek morfologisnya, semisal dari keberadaan kata – kata infleksi. Penelitian ini bertujuan untuk menelaah kata – kata infleksi serta jenis - jenisnya di dalam dongeng bahasa inggris anak – anak yang kemudian bisa dijadikan sebagai indikator tingkat kesulitan sebuah cerita serta mengetahui fungsi kata- kata infleksi tersebut dalam dongeng.  Penelitian ini menerapkan metode kualitatif deskriptif dengan analisis dokumen sebagai pendekatannya. Data diambi dari beberapa dongen berbahasa Inggris yang kemudian dianalisis dengan menerapkan teori infleksi dari Booij (2008).Penelitian ini menunjukkan bahwa infleksi verba serta infleksi adjektiva,secara,berurutan, merupakan jenis infleksi yang paling banyak ditemukan. Hal ini menunjukan bahwa cerita anak lebih menitikberatkan pada penggambaran  serta prilaku dari sang tokoh yang ada dalam cerita.. Selain itu, panjang pendeknya cerita berbanding lurus dengaan jumlah kata- kata infleksinya.Kata Kunci: kata-kata Infleksional, Dongeng anak-anak, Morfologi.